MANGKUNEGARA IV, RAJA-PENGUSAHA, PENDIRI INDUSTRI GULA MANGKUNEGARAN (1861-1881 - . Wasino (Humaniora, 2005)
This article will analyze the history of sugar plantation owned by the indegenious people, Mangkunegara, Colomadu and Tasik Madu . Historical sources are mostly taken from archives and library of Rekso Pustoko Mangkunegaran . Other sources are also collected from National Archive Jakarta, National Library Jakarta and a number of library in Yogyakarta. Research findings indicate that the Mangkunegaran sugar industry from the beginning represented the personal company of Mangkunegara IV which then was turned into a state (praja) company The establishment of Mangkunegaran sugar industry was a reaction to the wide-spead establishment of Western private enterprise in the region in mid XIX century. Mangkunegaran sugar industry was a traditional industry which was intended to boast up the Mangkunegaran's bargaining position to other Javanese kings .